An audit of uterotonic use for the prophylaxis and treatment of haemorrhage at caesarean delivery at Mowbray Maternity Hospital, Cape Town, South Africa - Pheto, Peloentle (Department of Obstetrics and Gynaecology, 2019)
Obstetric Haemorrhage is the leading cause of maternal death globally (1) and the third leading cause of death in South Africa (2). Concern has been expressed in South Africa that bleeding associated with caesarean delivery (CD) accounts for one-third of haemorrhage deaths and this has increased over the last ten years (3). The underlying cause of bleeding at CD is commonly uterine atony, and the majority of the CDs were performed at district hospitals (2,3,4). The Saving Mothers Reports describe inadequate use and documentation of uterotonics to prevent or treat bleeding at CD and have promoted the development of a standardised national protocol. While there is international agreement on the dosage and administration route for oxytocin to prevent OH after vaginal delivery, there is lack of consensus or standardisation of protocols for its prophylactic use at CD, with marked differences between country and facility protocols. Anaesthetists are concerned about the hypotensive effect of high dose intravenous boluses of oxytocin, particularly in women under spinal anaesthesia, and some maternal mortalities in the United Kingdom have been partially attributed to this (5). Hence it is important to balance safety with efficacy by promoting the lowest effective doses to minimise side effects but enable uterine contraction. Aim: The aim of this study was to perform a clinical audit of the documented use of uterotonics at CD at MMH to see how it adheres to the national protocol; and as a secondary outcome to measure the rate of haemorrhage at CD. Methods: This was a retrospective folder review of women who delivered by CD at MMH during the months of June and July 2017, including both elective and emergency operations. Information was obtained from women’s folders kept in the medical records department, using especially designed data extraction sheets. Data analysis was by simple descriptive statistics. Results: Three hundred and nineteen (319) folders from the study period were interrogated. This included 239 emergency CDs (75%) and 80 elective CDs (25%). They were all performed by obstetric registrars or medical officers with 89% being done under spinal anesthesia. Prophylactic oxytocin boluses at CD were given in 302 (94.7%) women but there was no documentation of its use in 17 (5.3%). One of the 302 women had a high dose IV bolus (7.5 IU) but the remainder had boluses below 5 IU. There were 75 women (23.5%) patients who received the national recommended dose of 2.5 IU IVI while 227 (71.1%) received alternative low dose boluses which were all less than 5 IU. The dose most commonly given was 3 IU; to 169 patients (53%) as a single or divided dose. There was wide variation in the dosage of prophylactic infusions with only 18 (5.6%) patients receiving the recommended intraoperative 7.5 IU infusion, while 221 (66.5%) received alternate infusion doses. Only 49 (15%) were discharged from theatre recovery to the postnatal ward with a prophylactic infusion running. In total 65 (20.4%) of the women received a 20 IU oxytocin infusion but it was unclear whether this was for prophylaxis or treatment. No intramuscular doses of oxytocin or syntometrine were given for prophylaxis. Among the 319 CDs, 13 (4.1%) had documented blood loss over 1000 ml and 24 (7.5%) had uterine atony reported by the surgeon. The most common treatment was 20 IU infusion followed by misoprostol (13 women), syntometrine (three women) and tranexamic acid (one woman). Additional surgical measures required were B-Lynch compression suture for one, and haemostatic sutures for two. There were no re-look laparotomies or hysterectomies during the study period and there were no major morbidity or mortalities from either CD or from anaesthetic complications. Discussion: Low dose bolus oxytocin and infusion is widely used at CD post fetal delivery at MMH, although the dose of 3 IU was most commonly used in contrast to the recommended 2.5 IU in the national protocol. There was variation in the usage and dosage of prophylactic oxytocin infusion. The rate of PPH in the subjects was low (4.1%) with the low dose prophylactic regimens used, suggesting that they were effective, although this may also have been contributed to by the skill of the surgeons. Consensus is needed among anaesthetists and standardisation of protocols on oxytocin prophylaxis at CD, particularly for training doctors working in district hospitals. Repeating this audit in district hospitals where there are higher CD case fatality rates would be important to shed light on practice in such facilities and improve healthcare delivery.